Low-Rank Tensor Structure of Solutions to Elliptic Problems with Jumping Coefficients (Journal of Computational Mathematics, 2018)
We study the separability properties of solutions to elliptic equations with piecewise constant coefficients in $\mathbb{R}^d, d \ge 2$. The separation rank of the solution to diffusion equation with variable coefficients is presented.